2006
DOI: 10.1177/08830738060210092201
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance in Children With Migraine

Abstract: The objectives of this study were to determine if (1) children with migraine experience greater sleep disturbances than their siblings, (2) those with more severe migraine have greater levels of sleep disruption, and (3) these sleep disturbances lead to greater behavioral problems and more missed school. Children aged 6 to 18 years with a diagnosis of migraine for > 6 months, who had at least one sibling without migraine in the same age range, were identified through our neurology clinic database or at the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 23 publications
1
51
2
Order By: Relevance
“…In accordance with the present findings, other studies have reported a higher prevalence of daytime sleepiness among migraineurs [16, 19, 26, 27] and insomnia among subjects with TTH [10, 13, 25]. Also our finding that a higher proportion of migraineurs with RLS had severe sleep disturbances accords with previous studies [52, 53].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with the present findings, other studies have reported a higher prevalence of daytime sleepiness among migraineurs [16, 19, 26, 27] and insomnia among subjects with TTH [10, 13, 25]. Also our finding that a higher proportion of migraineurs with RLS had severe sleep disturbances accords with previous studies [52, 53].…”
Section: Discussionsupporting
confidence: 93%
“…Other studies using different types of questionnaires have also reported a higher prevalence of sleep disturbances among migraineurs [16, 18, 19, 22, 26, 27], and subjects with TTH [10, 13, 25], respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Studies using behavioral assessments 26,45,50,68-70 , and PSG 16,53,66 in pediatric pain samples generally detected a relationship between high pain and disrupted sleep. In addition, most reviewed studies indicate that even after controlling for other factors, high pain is predictive of disrupted sleep patterns.…”
Section: Resultsmentioning
confidence: 99%
“…43-49 In a study of 69 adolescents with headache, 45 insufficient sleep, daytime sleepiness, difficulty falling asleep, and night awakenings were identified as frequent problems on the School Sleep Habits Questionnaire. 46 Using the CSHQ, 50 parents rated 6-18 year old children with migraine as having longer sleep durations, more daytime sleepiness, and longer sleep onset delays than healthy siblings. Findings from studies using actigraphy, wrist-watch size computers that monitor movement to identify sleep and wake patterns, 42 were mixed.…”
Section: Resultsmentioning
confidence: 99%
“…Sleep disturbances and poor sleep quality have been shown to be common in children and adolescents with migraine. 17,18 Maintaining a regular bedtime as well as sleep hygiene is recommended. Children should eat three meals per day at routine intervals.…”
Section: Non Pharmacologic Interventionsmentioning
confidence: 99%